2014
DOI: 10.5306/wjco.v5.i5.874
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in base excision repair genes: Breast cancer risk and individual radiosensitivity

Abstract: Breast cancer (BC) is the most common cancer among women worldwide. The aetiology and carcinogenesis of BC are not clearly defined, although genetic, hormonal, lifestyle and environmental risk factors have been established. The most common treatment for BC includes breast-conserving surgery followed by a standard radiotherapy (RT) regimen. However, radiation hypersensitivity and the occurrence of RT-induced toxicity in normal tissue may affect patients' treatment. The role of DNA repair in cancer has been exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…In particular, Arg399Gln SNP, the most common variant in the XRCC1 gene, is an important polymorphism related to sporadic breast cancer susceptibility. Nevertheless, literature data showed a weak association of this SNP with BC risk, that is stronger only within some ethnicities [25]. In general, the effect of SNPs on the occurrence of breast cancer and other tumour types is usually only slightly statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, Arg399Gln SNP, the most common variant in the XRCC1 gene, is an important polymorphism related to sporadic breast cancer susceptibility. Nevertheless, literature data showed a weak association of this SNP with BC risk, that is stronger only within some ethnicities [25]. In general, the effect of SNPs on the occurrence of breast cancer and other tumour types is usually only slightly statistically significant.…”
Section: Discussionmentioning
confidence: 90%
“…The genetic variants of DNA repair-related genes may affect the capacity of the DNA repair pathways. Insufficient DNA repair capacity leads to increased DNA damage and high tissue radiosensitivity, resulting in severe radiation-related complications (26,27).…”
Section: Dna Repair-related Genesmentioning
confidence: 99%
“…These strategies include the base excision and nucleotide excision DNA repair pathways. Base excision repair acts on single strand breaks, oxidized bases, and few bulky adducts [15,16], induced by endogenous free radicals or from exogenous exposure to genotoxic agents [17]. Previous data demonstrated that the expression of messenger RNA (mRNA) related to base excision repair is altered in biological tissues exposed to low-intensity red [18] and infrared [19,20] lasers.…”
Section: Introductionmentioning
confidence: 99%